2018
DOI: 10.3892/ol.2018.7817
|View full text |Cite
|
Sign up to set email alerts
|

Pro‑metastatic signaling of the trans fatty acid elaidic acid is associated with lipid rafts

Abstract: Abstract. Trans fatty acids (TFAs) are risk factors for cardiovascular disorders, and the cancer-promoting effects of TFAs have been previously reported. The present study examined the effects and signaling of elaidic acid (EA), a TFA, in colorectal cancer (CRC) cells. Oral intake of EA was found to increase metastasis of HT29 human CRC cells. Results indicated that, in the plasma membrane, EA was integrated into cholesterol rafts, which contain epidermal growth factor receptors (EGFR). EA increased nanog and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…In this study, biglycan overexpression was frequently observed in DM-CRC. Our data also showed that insulin induced biglycan production, with synergistic effects observed with simultaneous treatment with high concentration of glucose and pro-tumorous fatty acids, linoleic acid and elaidic acid [15,16,[47][48][49][50][51]. Such high levels of insulin, glucose, and fatty acids are associated with diabetic condition.…”
Section: Discussionsupporting
confidence: 69%
“…In this study, biglycan overexpression was frequently observed in DM-CRC. Our data also showed that insulin induced biglycan production, with synergistic effects observed with simultaneous treatment with high concentration of glucose and pro-tumorous fatty acids, linoleic acid and elaidic acid [15,16,[47][48][49][50][51]. Such high levels of insulin, glucose, and fatty acids are associated with diabetic condition.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, they found that EA increased the resistance of these cells to 5-fluorouracil [ 41 ]. Pro-metastatic effects of EA in CRC have been associated with activation of EGFR signaling in cholesterol-rich lipid rafts [ 42 ], While, it was showed that the use of DHA with taxane drugs suppressed genes related to NF-κB. The results of this study suggest that the use of DHA with a drug from the taxane group weakens the resistance of cancer cells to taxanes and increases their cytotoxic effect on prostate cancer cells [ 43 ].…”
Section: Discussionmentioning
confidence: 93%
“…Our data implicate for the first time a role for cholesterol synthesis in ADM. Although the mechanisms through which cholesterol acts remain to be determined, possibilities include regulation of hedgehog signaling (46), which has been implicated in acinar cell regeneration after injury and early carcinogenesis (47,48), or lipid rafts (49), which are cholesterol-rich and promote EGFR signaling (50)(51)(52). Cholesterol has also recently been shown to stimulate proliferation of intestinal stem cells and to promote tumor formation (53), suggesting that cholesterol metabolism might play similar roles in colon and pancreatic carcinogenesis.…”
Section: Researchmentioning
confidence: 99%